The structure of patella ligament of rats when it is fixed on different implants surfaces - Vyrva, Oleg; Ashukina, Nataliya; Skoryk, Ivan; Danyshchuk, Zinayda (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
The difficulties of the organ-preserving operations on the proximal tibia are associated with the need to cut off the patellar ligament during surgical access for ablastic tumor resection, which causes difficulties in restoring the function of the knee joint in the postoperative period. Objective: on experimental rats to determine the morphological features of the restoration of the patellar ligament after fixation on various surfaces of implants. Methods: thirty white laboratory male rats (age 6–7 months, weight 290–380 g) were divided into 3 groups, depending on the implant: I — stainless steel coated with microporous polyethylene terephthalate (Attachment tube), II — titanium coated with corundum ceramics, III — titanium. Implants were inserted into the Attachment area of the patellar ligament on the tibia, the patellar ligament was sutured and refixed 1 mm distal to the implant. The histological analysis was performed after 15 and 90 days. Results: the formation of close contact between the Attachment tube material and the granulation and connective tissues that formed in the area of the patellar ligament injury was found. During the reorganization of the regenerate 3 months after the injury, tendon-like tissue was formed. It contained type I collagen, which was not observed in animals of groups II and III. So, in group II, degenerative changes caused to the formation of the loose connective tissue on 70 % the patella ligament 3 months after surgery, in group III — cartilaginous, loose connective and adipose tissue. Type III collagen predominated in these tissues. Conclusions: the use of the Attachment tube is the most effective for refixing and restoring the function of the extensor mechanism of knee joint after resection of the proximal tibia tumors and the replacement of the bone-articular defect with a modular endoprosthesis.